Clinical profile and risk factors in neonatal septicemiaa - P.MAHARAJA,; V .MANGAYAKARASI, (International Journal of Pharma and Bio Sciences, 2017)
Aim of the study to find out the correlation clinical profile and risk factors for neonatal sepsis with culture proven cases. The present study was intended to know the incidence and mortality rate of neonatal sepsis among Hospital admission. Neonatal sepsis is single most important cause of Neonatal death globally. The incidence of neonatal sepsis in india is 30/1000 live birth. The prospective study was conducted on 32 neonates on consecutive birth, fulfilling the inclusion and Exclusion criteria subjected to sepsis screening. Blood Culture and sepsis screen was carried out 32 neonates. Out of 32 neonates with clinical features of sepsis 3 where blood culture breathlessness and Temperature instability were significant positive. Sepsis screen was carried out with total leucocytes count, absolute neutrophils count, CRP, Thromphocyte estimation. The identification of Causative organism was carried out by standard identification test.Among the risk factors breathlessness and temperature instability were significant. Among the clinical feature 70% neonates with grunting and temperature instability were proven sepsis. In this study, Out of 32 clinical neonatal sepsis 3(9.38%) where culture positive among isolates 2 gram negative bacilli and one is MR CONS.Blood Culture and sepsis screen should be carried out in neonates suspected of sepsis. However culture report is available only after 5-7 days. Neonatal sepsis is common in new born with non specific symptamatology Causing difficulty in diagnosis early and prompt detection and appropriate treatment in neonatal sepsis can significantly reduce morbidity and mortality.